Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 45240 by maxmathsup by imad last updated on 10/Oct/18

calculate Σ_(n=2) ^∞   ((2n+1)/(n^4 −n^2 ))

calculaten=22n+1n4n2

Commented by maxmathsup by imad last updated on 11/Oct/18

let decompose F(x)=((2x+1)/(x^4 −x^2 )) =((2x+1)/(x^2 (x−1)(x+1))) ⇒  F(x)=(a/x) +(b/x^2 ) +(c/(x−1)) +(d/(x+1))  b =lim_(x→0) x^2 F(x) =−1  c =lim_(x→1) (x−1)F(x)=(3/2)  d =lim_(x→−1) (x+1)F(x) =((−1)/(−2)) =(1/2) ⇒F(x)=(a/x) −(1/x^2 ) +(3/(2(x−1))) +(1/(2(x+1)))  F(2) = (5/(4.3)) =(5/(12)) =(a/2) −(1/4) +(3/2) +(1/6)  ⇒5 =6a−3 +18 +2 ⇒5=6a +17 ⇒  6a=−12 ⇒a =−2 ⇒F(x)=−(2/x) −(1/x^2 ) +(3/(2(x−1))) +(1/(2(x+1)))  let S_n =Σ_(k=2) ^∞  ((2k+1)/(k^4 −k^2 )) ⇒S_n =Σ_(k=2) ^n  F(k)  =−2 Σ_(k=2) ^n  (1/k) −Σ_(k=2) ^n  (1/k^2 ) +(3/2) Σ_(k=2) ^n  (1/(k−1)) +(1/2)Σ_(k=2) ^n  (1/(k+1)) but  Σ_(k=2) ^n  (1/k)=H_n −(3/2)  Σ_(k=2) ^n  =ξ_n (2)−1  Σ_(k=2) ^n  (1/(k−1)) =Σ_(k=1) ^(n−1)  (1/k) =H_(n−1)   Σ_(k=2) ^n   (1/(k+1)) =Σ_(k=3) ^(n+1)  (1/k)=H_(n+1)  −1−(1/2)−(1/3) =H_(n+1) −(3/2) −(1/3) =H_(n+1) −((11)/6) ⇒  S_n =−2H_n   +3  +ξ_n (2)−1 +(3/2) H_(n−1)  +(1/2) H_(n+1) −((11)/(12))  =−2H_n  +(3/2) H_(n−1) +(1/2) H_(n+1)  +ξ_n (2)+2−((11)/(12)) ⇒  S_n  =−2(ln(n) +γ +o((1/n)))+(3/2)( ln(n−1)+γ +o((1/n)))+(1/2)(ln(n)+γ +o((1/n)))+ξ_n (2)+((13)/(12))  =−2ln(n) +(3/2)ln(n−1) +(1/2)ln(n) +o((1/n)) +ξ_n (2)+((13)/(12))  =ln((√((n−1)^3 ))(√n))−ln(n^2 ) +o((1/n))+ξ_n (2)+((13)/(12))  =ln{(((n−1)(√(n(n−1))))/n^2 )}+o((1/n))+ξ_n (2)+((13)/(12)) ⇒  lim_(n→+∞)  S_n =ξ(2)+((13)/(12)) =(π^2 /6) +((13)/(12)) .

letdecomposeF(x)=2x+1x4x2=2x+1x2(x1)(x+1)F(x)=ax+bx2+cx1+dx+1b=limx0x2F(x)=1c=limx1(x1)F(x)=32d=limx1(x+1)F(x)=12=12F(x)=ax1x2+32(x1)+12(x+1)F(2)=54.3=512=a214+32+165=6a3+18+25=6a+176a=12a=2F(x)=2x1x2+32(x1)+12(x+1)letSn=k=22k+1k4k2Sn=k=2nF(k)=2k=2n1kk=2n1k2+32k=2n1k1+12k=2n1k+1butk=2n1k=Hn32k=2n=ξn(2)1k=2n1k1=k=1n11k=Hn1k=2n1k+1=k=3n+11k=Hn+111213=Hn+13213=Hn+1116Sn=2Hn+3+ξn(2)1+32Hn1+12Hn+11112=2Hn+32Hn1+12Hn+1+ξn(2)+21112Sn=2(ln(n)+γ+o(1n))+32(ln(n1)+γ+o(1n))+12(ln(n)+γ+o(1n))+ξn(2)+1312=2ln(n)+32ln(n1)+12ln(n)+o(1n)+ξn(2)+1312=ln((n1)3n)ln(n2)+o(1n)+ξn(2)+1312=ln{(n1)n(n1)n2}+o(1n)+ξn(2)+1312limn+Sn=ξ(2)+1312=π26+1312.

Answered by ajfour last updated on 11/Oct/18

Σ_(n=2) ^∞   ((2n+1)/(n^2 (n−1)(n+1)))  =Σ(((n+1)+(n−1))/((n−1)nn(n+1)))+(1/2)Σ(((n+1)−(n−1))/((n−1)nn(n+1)))  =Σ(1/((n−1)n^2 ))+Σ(1/(n^2 (n+1)))           +(1/2)Σ(1/((n−1)n^2 ))−(1/2)Σ(1/(n^2 (n+1)))  =(3/2)Σ(1/((n−1)n^2 ))+(1/2)Σ(1/(n^2 (n+1)))  =(3/4)Σ((1/((n−1)n))−(1/n^2 ))+(1/4)Σ((1/n^2 )−(1/(n(n+1))))  =(3/4)Σ((1/(n−1))−(1/n))−(1/4)Σ((1/n)−(1/(n+1)))             −(1/2)Σ(1/n^2 )  =(3/4)(1−(1/2)+(1/2)−(1/3)+..)−(1/4)((1/2)−(1/3)+(1/3)−(1/4)+..)             −(1/2)((1/4)+(1/9)+...)   = (3/4)−(1/8)−(1/2)((1/4)+(1/9)+(1/(16))+..)  ln (1−x)=−(x+(x^2 /2)+(x^3 /3)+...)  ∫_0 ^(  1)  ((ln (1−x))/x)dx=−(1+(1/4)+(1/9)+(1/(16))+..)  so   Σ_(n=2) ^∞   ((2n+1)/(n^4 −n^2 )) = (3/4)−(1/8)−(1/2)[1+∫_0 ^(  1) ((ln (1−x))/x)dx]  ..... (cant solve the integral, sir ).

n=22n+1n2(n1)(n+1)=Σ(n+1)+(n1)(n1)nn(n+1)+12Σ(n+1)(n1)(n1)nn(n+1)=Σ1(n1)n2+Σ1n2(n+1)+12Σ1(n1)n212Σ1n2(n+1)=32Σ1(n1)n2+12Σ1n2(n+1)=34Σ(1(n1)n1n2)+14Σ(1n21n(n+1))=34Σ(1n11n)14Σ(1n1n+1)12Σ1n2=34(112+1213+..)14(1213+1314+..)12(14+19+...)=341812(14+19+116+..)ln(1x)=(x+x22+x33+...)01ln(1x)xdx=(1+14+19+116+..)son=22n+1n4n2=341812[1+01ln(1x)xdx].....(cantsolvetheintegral,sir).

Answered by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

((2n+1)/(n^2 (n+1)(n−1)))=(a/n)+(b/n^2 )+(c/(n+1))+(d/(n−1))  2n+1=an(n+1)(n−1)+b(n+1)(n−1)+cn^2 (n−1)+dn^2 (n+1)  put n=0   1=b(−1)  b=−1  put n−1=0  3=d×1×2   d=(3/2)  put n+1=0  −2+1=c×(−1)^2 ×(−2)  −1=−2c   c=(1/2)  2n+1=an(n+1)(n−1)+b(n+1)(n−1)+cn^2 (n−1)+dn^2 (n+1)  2n+1=a(n^3 −n)+(−1)(n^2 −1)+(1/2)n^2 (n−1)+(3/2)n^2 (n+1)  2n+1=n^3 (a+(1/2)+(3/2))+n^2 (−1−(1/2)+(3/2))+n(−a)+1  a+2=0  a=−2  =Σ_(n=2) ^∞ (((−2)/n)+((−1)/n^2 )+((1/2)/(n+1))+((3/2)/(n−1)))  =S_1 +S_2 +S_3 +S_4   S_1 =−2Σ_(n=2) ^∞ (1/n)  S_1 =−2{((1/1)+(1/2)+(1/3)+...∞)−(1/1)}       =−2(γ−1)=−2γ+1  γ=Eulers constant  S_2 =−1Σ_(n=2) ^∞ (1/n^2 )          =−1{((1/1^2 )+(1/2^2 )+(1/3^2 )+..∞)−(1/1)}             =−((π^2 /6)−1)=1−(π^2 /6)  S_3 =(1/2)Σ_(n=2) ^∞  (1/(n+1))          =(1/2){((1/1)+(1/2)+(1/3)+...∞)−((1/1)+(1/2))}           =(1/2)(γ−(3/2))=(γ/2)−(3/4)  S_4 =(3/2)Σ_(n=2) ^∞  (1/(n−1))       (3/2)((1/1)+(1/2)+(1/3)+...)       =((3γ)/2)  so reauired ans is S_1 +S_2 +S_3 +S_4   =(−2γ+1)+(1−(π^2 /6))+((γ/2)−(3/4))+(((3γ)/2))  =−2γ+2γ+1+1−(3/4)−(π^2 /6)  =(5/4)−(π^2 /6)   pls check...

2n+1n2(n+1)(n1)=an+bn2+cn+1+dn12n+1=an(n+1)(n1)+b(n+1)(n1)+cn2(n1)+dn2(n+1)putn=01=b(1)b=1putn1=03=d×1×2d=32putn+1=02+1=c×(1)2×(2)1=2cc=122n+1=an(n+1)(n1)+b(n+1)(n1)+cn2(n1)+dn2(n+1)2n+1=a(n3n)+(1)(n21)+12n2(n1)+32n2(n+1)2n+1=n3(a+12+32)+n2(112+32)+n(a)+1a+2=0a=2=n=2(2n+1n2+12n+1+32n1)=S1+S2+S3+S4S1=2n=21nS1=2{(11+12+13+...)11}=2(γ1)=2γ+1γ=EulersconstantS2=1n=21n2=1{(112+122+132+..)11}=(π261)=1π26S3=12n=21n+1=12{(11+12+13+...)(11+12)}=12(γ32)=γ234S4=32n=21n132(11+12+13+...)=3γ2soreauiredansisS1+S2+S3+S4=(2γ+1)+(1π26)+(γ234)+(3γ2)=2γ+2γ+1+134π26=54π26plscheck...

Commented by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

Commented by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

Commented by ajfour last updated on 11/Oct/18

sir please explain me how  Σ_(n=1) ^∞  (1/n^2 ) = (π^2 /6) .

sirpleaseexplainmehown=11n2=π26.

Commented by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

Commented by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

Commented by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

Commented by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

Commented by tanmay.chaudhury50@gmail.com last updated on 11/Oct/18

proof taken from SL Loney Trigonometry

prooftakenfromSLLoneyTrigonometry

Terms of Service

Privacy Policy

Contact: info@tinkutara.com